Phytochemical-assisted Synthesis of Titania Nanoparticles using Azadirachta indica Leaf Extract as Photocatalyst in the Photodegradation of Methyl Orange - Imad Eddine Aouissi; Norazah Basar; Wan Nazihah Wan Ibrahim; Sheela Chandren (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
The biosynthesis procedure for nanomaterial preparation is a promising alternative due to its simplicity and environmental friendliness. In this work, TiO2 NPs were biosynthesized using the aqueous leaf extract of Azadirachta indica. The influence of the extract volumes, solvents, and acetic acid on the properties of TiO2 NPs was studied. Phytochemical screening and ATR-FTIR spectrum confirmed the presence of phenolic compounds in the leaf extract. XRD patterns showed that the samples were mainly in the anatase phase. However, for the water-based samples and when 1 and 2 mL of extract volumes were used, anatase/brookite mixture was observed. FESEM images displayed almost spherical and agglomerated NPs. UV-Vis-NIR studies showed that the samples’ bandgaps values are within the range of anatase TiO2. The photocatalytic activity of the TiO2 NPs was evaluated in the photodegradation of methyl orange (MO) under UV light irradiation. The water-based sample synthesized using 2 mL of the extract achieved 98.62% of MO degradation within 270 min and demonstrated the highest pseudo-first-order photodegradation kinetic constant of 0.0147 min-1. These results indicate that the use of the plant-based biosynthesis method with water as the solvent successfully produced TiO2 NPs with good physicochemical properties and photocatalytic activity in the photodegradation of organic dye. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).